Design And Construction Of A Simple Incinerator For Household Waste Combustion - Syafrizal Fachri Aziz; Arif Marwanto (Journal of Applied Mechanical Engineering Innovation, 2026)
This study aimed to design and construct a simple incinerator that produces minimal smoke, is easy to operate, and performs effectively for household waste combustion. The research used a research and development (R&D) method with the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation. At the design stage, five main components were produced: a combustion furnace with dimensions of 360 mm × 590 mm, a frame of 360 mm × 360 mm × 500 mm, a boiler, a fuel container, and a furnace cover. The development stage included fabrication, assembly, and finishing, while the implementation stage involved performance testing using cardboard waste and dry teak leaves, each tested twice with a mass of 2 kg and used oil as fuel. The results showed that the incinerator burned cardboard waste at a combustion rate of 9.545 kg/hour and dry teak leaves at 10.67 kg/hour. The combustion process reached a reported summary temperature of 1075°C. The waste reduction effectiveness was 89.5% for cardboard waste and 91.5% for teak leaves, with an average effectiveness of 90.5%. These results indicate that the device can be used as a controlled small-scale combustion system for household waste management.